1994
DOI: 10.1524/zkri.1994.209.6.479
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the Fe4Al13 structure and its relationship to the quasihomological homeotypical structures

Abstract: The crystal structure of Fe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
2
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(94 citation statements)
references
References 9 publications
7
77
2
8
Order By: Relevance
“…X-ray diffraction patterns obtained with use of two independent instruments (JEOL JDX-7S -Cu Kα 1 radiation, Philips X-PERT -Cu Kα 1 radiation) for non-treated and annealed samples (Figures 5a and 5b respectively) show however only the presence of an eutectic zinc alloy and a steel substrate but neither the orthorhombic Fe 2 Al 5 Zn x nor the monoclinic FeAl 3 Zn x (Fe 4 Al 13 Zn x ) have been revealed (see the respective reference patterns in Figure 5c simulated upon the data from references [4] and [12]). Since the transition layer thickness is low (below 1 µm) and consequently its volume is much lower than the alloy coating volume, X-ray diffraction peaks corresponding to the interface components should have low intensities.…”
Section: Xrd Studiesmentioning
confidence: 85%
See 1 more Smart Citation
“…X-ray diffraction patterns obtained with use of two independent instruments (JEOL JDX-7S -Cu Kα 1 radiation, Philips X-PERT -Cu Kα 1 radiation) for non-treated and annealed samples (Figures 5a and 5b respectively) show however only the presence of an eutectic zinc alloy and a steel substrate but neither the orthorhombic Fe 2 Al 5 Zn x nor the monoclinic FeAl 3 Zn x (Fe 4 Al 13 Zn x ) have been revealed (see the respective reference patterns in Figure 5c simulated upon the data from references [4] and [12]). Since the transition layer thickness is low (below 1 µm) and consequently its volume is much lower than the alloy coating volume, X-ray diffraction peaks corresponding to the interface components should have low intensities.…”
Section: Xrd Studiesmentioning
confidence: 85%
“…It can be interesting to quote some figures concerning zinc solubility in the Fe-Al intermetallics. They vary from 21 wt.% [7] to 22.87 wt.% [11] for the orthorhombic Fe 2 Al 5 phase and achieve 13.92 wt.% for the monoclinic FeAl 3 (Fe 4 Al 13 ) phase [12]. It could be interesting to illustrate a microstructure evolution of the Galfan coating subjected to the heat treatment in air (600 • C/5 min.)…”
Section: Introductionmentioning
confidence: 99%
“…1 It should be mentioned that the phase Fe 4 Al 13 originally was denoted as FeAl 3 in the old literature, even though already in 1955 Black [10] found that the true composition corresponds to a formula Fe 4 Al 13 . Only since Grin et al [9] published their structure refinement of this phase in 1994, the formula Fe 4 Al 13 is generally accepted in the literature. [15] to 1166°C.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…It adopts an own structure type with no obvious structural relations to the adjacent phases in the binary system [2][3][4][5][6]. Important common structural motifs of these compounds, like the existence of condensed pentagonal prismatic channels [7] or the existence of a ²cluster² formed by two trigonal prisms around cobalt and a distorted rectangular prism around aluminum [8] are not found in the title compound. One possibility to visualize the complex structure of the g phase is based on the coordination of Co atoms.…”
Section: Discussionmentioning
confidence: 99%